2004
DOI: 10.1176/appi.ajp.161.5.882
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell Loss in the Anterior Cingulate Cortex, a Subregion of the Prefrontal Cortex, in Subjects With Schizophrenia

Abstract: A selective reduction in glial cells in Brodmann's area 24 (but not in area 32) is seen in brains of subjects with schizophrenia relative to those of comparison subjects. Further investigations of the glial cells, their mutual relationship, and their relationship with neurons are needed to understand the role of specific glial components in this mental disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
111
1
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(129 citation statements)
references
References 38 publications
12
111
1
5
Order By: Relevance
“…Interestingly, similar to the findings of the present study, post-mortem studies in schizophrenia subjects have revealed smaller volumes of frontal, parietal, and temporal cortices (Pakkenberg, 1993;Selemon et al, 2002), lower glial cell (area 24) (Stark et al, 2004) and oligodendrocyte number (area 9) (Hof et al, 2003), higher neuron density in the dorsolateral prefrontal (area 9), anterior cingulate (area 24), and primary visual (area 17) cortices (Chana et al, 2003;Selemon et al, 1995), and no change in total neuron number in the prefrontal (Thune et al, 2001) or total neocortex (Pakkenberg, 1993) relative to normal comparison subjects. However, whereas treatment with typical antipsychotics has been reported to lead to smaller volumes in certain cortical areas in subjects with schizophrenia (Dazzan et al, 2005;Lieberman et al, 2005), atypical antipsychotics might preserve cortical volume (Dazzan et al, 2005) or slow the rate of volume decreases (Lieberman et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, similar to the findings of the present study, post-mortem studies in schizophrenia subjects have revealed smaller volumes of frontal, parietal, and temporal cortices (Pakkenberg, 1993;Selemon et al, 2002), lower glial cell (area 24) (Stark et al, 2004) and oligodendrocyte number (area 9) (Hof et al, 2003), higher neuron density in the dorsolateral prefrontal (area 9), anterior cingulate (area 24), and primary visual (area 17) cortices (Chana et al, 2003;Selemon et al, 1995), and no change in total neuron number in the prefrontal (Thune et al, 2001) or total neocortex (Pakkenberg, 1993) relative to normal comparison subjects. However, whereas treatment with typical antipsychotics has been reported to lead to smaller volumes in certain cortical areas in subjects with schizophrenia (Dazzan et al, 2005;Lieberman et al, 2005), atypical antipsychotics might preserve cortical volume (Dazzan et al, 2005) or slow the rate of volume decreases (Lieberman et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Because of the magnitude of the volume reduction in the parietal lobe, it offered the best opportunity to answer this question. In addition, the answer to this question might be particularly informative given the findings that, in at least some cortical regions, schizophrenia is associated with lower glial cell number (Hof et al, 2003;Stark et al, 2004) without a change in neuron number (Pakkenberg, 1993;Thune et al, 2001). In order to address this question, an unbiased stereological design was used to estimate the total numbers and densities of neuronal, glial, and endothelial cells in the gray matter of the left parietal lobe from the same cohort of monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several psychiatric disorders have been reported to have decreased glia cell number or density (Cotter et al, 2001(Cotter et al, , 2002Rajkowska et al, 2001;Hof et al, 2003;Stark et al, 2004). However, additional studies are needed to determine whether these observed glial changes are specific to the respective diseases or related to treatment with antipsychotic drugs.…”
Section: Potential Sources Of the Observed Reductions In Brain Volumementioning
confidence: 99%
“…Although several post-mortem studies have found no evidence of cortical neuronal loss (Pakkenberg, 1993;Selemon et al, 1995;Akbarian et al, 1995), other studies indicate layer-specific reductions of interneuron (Benes et al, 1991(Benes et al, , 2001) and glial cell density (Cotter et al, 2002;Stark et al, 2004) in several cortical areas. Taken together, these data have led to the hypothesis that apoptosis could contribute to the loss of cortical volume in schizophrenia (Margolis et al, 1994;Jarskog et al, 2005).…”
Section: Introductionmentioning
confidence: 98%